191 Evaluation of Diverse Cool-Season Grass Mixtures with red Clover on Ruminal Fermentation in Continuous Culture. (21st September 2022) - Snider, Miriam A; Mulakala, Bharath K; Driemel, Ashley W; Ziegler, Sara E; Darby, Heather M; Soder, Kathy J; Brito, Andre F; Greenwood, Sabrina L
Abstract: Dual-flow continuous culture fermenters were used to evaluate the impacts of forage mixtures on ruminal fermentation. Diets (DM basis) contained 40% red clover combined with 1) 60% orchardgrass (OG); 2) 30% orchardgrass + 30% meadow fescue (MF); 3) 20% orchardgrass + 20% meadow fescue + 20% Kentucky bluegrass (KYBG); or 4) 15% orchardgrass + 15% meadow fescue + 15% Kentucky bluegrass + 15% perennial ryegrass (PRG). Treatments were randomly assigned to fermenters in a 4 x 4 Latin square design. Each 10-d period included a 7-d adaptation and 3-d sampling period. Diets (110 g DM/d) were added across 4 feedings/d (33% each, 0700 h and 1600 h; 17% each, 0820h and 1720 h). Fermenter pH was recorded continuously for 10-d. Methane was measured on d 7-10 at 0630 and 1530 h. Effluent samples were collected on d 8-10. Results were analyzed using PROC GLIMMIX of SAS with significance at P ≤ 0.05. Apparent digestibility of DM, OM, NDF, and ADF was greatest (P ≤ 0.05) for fermenters receiving KYBG, followed by PRG. Apparent DM and OM digestibility for OG and MF were less than KYBG by 18.0% and 19.6%, respectively. Fermenters receiving KYBG spent the greatest amount of time under pH 5.8 (avg. 15.5 h/d; P = 0.0004). Acetate:propionate and acetate + butyrate:propionate ratios were greater for fermenters receiving KYBG (4.09 and 4.71) and PRG (4.03 and 4.65; P < 0.0001). Water soluble carbohydrate concentration of effluent was least for KYBG (0.80 mg/ mL; P ≤ 0.05). Methane output for KYBG (116.8 mg/dL; P < 0.0001) was greater than that of OG (13.7 mg/dL), MF (31.7 mg/dL), and PRG (11.9 mg/dL) which did not differ from one another. These results suggest that diets containing KYBG and PRG were more digestible with PRG having the added benefit of decreased methane output.